The Impact of Cardiac Dysfunction Based on Killip Classification on Gastrointestinal Bleeding in Acute Myocardial Infarction - Liu, Yu; Feng, De-Jing; Wang, Le-Feng; Liu, Li-Hong; Ren, Zheng-Hong; Hao, Jian-Yu; Li, Kui-Bao; Chen, Mu-Lei (Frontiers in Medicine, 2022)
Background: Owing to limited data, the effect of cardiac function by every Killip classification on gastrointestinal bleeding (GIB) in patients with acute myocardial infarction (AMI) is unclear. The present study aimed to investigate the impact of cardiac function by Killip classification on GIB in patients with AMI and determine if patients in higher Killip classes are more prone to GIB. Methods: This retrospective study comprised patients with AMI who were admitted to the cardiac intensive care unit (CICU) in the heart center of the Beijing Chaoyang Hospital between December 2010 and June 2019. The in-hospital clinical data of the patients were collected. GIB and cardiac function, according to the Killip classification system, were confirmed using the discharge diagnosis of the International Classification of Diseases, Tenth Revision coding system (ICD 10). Univariate and multivariate conditional logistic regression models were constructed to test the association between GIB and cardiac function by Killip classification, as determined by the Killip classes. Results: In total, 6,458 patients with AMI were analyzed, and GIB were diagnosed in 131 patients (2.03%). The multivariate logistic regression analysis showed that the risk of GIB was significantly correlated with cardiac function (Killip class 2 vs. 1: odds ratio [OR] = 1.15, 95% confidence interval [CI]: 0.73–1.08; Killip class 3 vs. 1: OR = 2.63, 95% CI: 1.44–4.81; and Killip class 4 vs. 1: OR = 4.33, 95% CI: 2.34–8.06). Conclusions: This study demonstrates that cardiac function is an independent predictor of GIB when the Killip class is ≥3. Therefore, higher Killip classes are associated with an increased risk of developing GIB.